Marriage - Stefoff, Rebecca, 1951- (New York : Marshall Cavendish Benchmark, 2007)
Examines the history of marriage, changes in the purposes of marriage through the centuries, changes in family structures, and the debate over same-sex marriage, and discusses whether marriage will die out in the future.
Weddings and questions -- The roots of matrimony -- The romance revolution -- Family matters -- Same-sex unions -- The future of marriage.
Includes bibliographical references (p. 131-132) and index.
Wilson's Junior High School, August 2007
School Library Journal, April 2007
Young Adult
Keywords: Marriage